COVID-19 Vaccine–Associated Takotsubo Cardiomyopathy. (May 2021) - Jani, Chinmay; Leavitt, Jeffrey; Al Omari, Omar; Dimaso, Alana; Pond, Kyle; Gannon, Stephen; Chandran, Arun Kumar; Dennis, Christopher; Colgrove, Robert
Abstract : Supplemental Digital Content is Available in the Text.